2017
DOI: 10.1136/bjsports-2016-097403
|View full text |Cite
|
Sign up to set email alerts
|

What domains of clinical function should be assessed after sport-related concussion? A systematic review

Abstract: The overall quality of the studies was considered low. The absence of an objective, gold standard criterion makes the accurate diagnosis of SRC challenging. Current approaches tend to emphasise cognition, symptom assessment and postural stability with less of a focus on other domains of functioning. We propose that the clinical assessment of SRC should be symptom based and interdisciplinary. Whenever possible, the SRC assessment should incorporate neurological, vestibular, ocular motor, visual, neurocognitive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 79 publications
1
70
0
3
Order By: Relevance
“…Diagnosing a SRC with specificity, sensitivity, and in real time continues to pose a challenge simply because concussion remains purely a clinical diagnosis based on an assessment of signs and symptoms along with an evaluation of cognitive, vestibular and oculomotor functions 16. To date, there is no specific biomarker, biomechanical technology or neuroimaging technique that can be utilised for the unequivocal diagnosis of a SRC 17.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing a SRC with specificity, sensitivity, and in real time continues to pose a challenge simply because concussion remains purely a clinical diagnosis based on an assessment of signs and symptoms along with an evaluation of cognitive, vestibular and oculomotor functions 16. To date, there is no specific biomarker, biomechanical technology or neuroimaging technique that can be utilised for the unequivocal diagnosis of a SRC 17.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that these tools appear to lose utility when used for initial assessment more than 3–5 days after the injury 2 . Some computerised neurocognitive tests are validated for use in concussion although they seem to offer no advantage over the abbreviated cognitive component of the SCAT5 6 . Nevertheless, none of these tools should be used in isolation.…”
Section: Boxmentioning
confidence: 99%
“…The most recent meeting of the CISG took place in Berlin in October 2016 and the outcomes were released as a consensus statement in April 2017, 2 accompanied by a series of systematic reviews covering many aspects of concussion research and management. [3][4][5][6][7] It was therefore necessary to update the AISeAMA position statement to incorporate several aspects of concussion detection tools and management guidelines arising from the Berlin consensus. We also incorporated our own analysis of the evidence 8 and discussed the position statement with representatives from several contact and collision sports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The clinical diagnosis of SRC relies on an assessment of signs and symptoms and an evaluation of cognitive, neurologic, vestibular, and oculomotor functions. 4 This is often complicated by the fast pace of the game, the multiple players involved, limited or obfuscated views of the field, and the availability of trained health care providers, leading to a risk of missed sideline detection of concussion. 5 As described by attendees at the Dublin meeting, ''television coverage and commentary of injuries in collision sport and the high profile of concussion as a public health issue, has placed medical management and return to sport decisions under increased scrutiny.''…”
mentioning
confidence: 99%